تأثير تكنولوجيات الاعلام والاتصال على الهوية الثقافية في مجتمعات الشتات - سغيري, وهيبة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
يعود ظهور مفهوم الشتات إلى منتصف تسعينات القرن الماضي فمجتمعات الشتات تكون جزءا من النسيج الاجتماعي لدول المقصد، ومع ذلك فهذه المجتمعات في بحث مستمر عن الطرق المثلى للحفاظ على هويتها الثقافية وانتمائها للوطن الأم مع محاولة الإندماج مع الثقافات المختلفة للحفاظ على نظامها الإجتماعي، تبحث الدراسة في مدى مساهمة تكنولوجيا الإعلام في الحفاظ على الهوية الثقافية والعلاقات عبر وطنية للمغتربين في مجتمعات المقصد، وخلصت إلى أن تكنولوجيات الإتصال ساهمت في الحفاظ على هوية المغتربين وصهرهم ثقافيا نسبيا في المجتمعات المحلية، إلا أنها عملت في نفس الوقت على استبعاد هذه الأقليات مما يزيد من حدة التوترات الإيديولوجية والثقافية وأيضا ظهور مفاهيم جديدة زادت من قوة مفهوم الشتات. Abstract: The emergence of the concept of diaspora dates back to the mid-1990s, as diaspora communities are part of the social fabric of destination countries.These societies are in constant search for optimal ways to preserve their cultural identity and belonging to the motherland, In addition to trying to integrate with different cultures to maintain their social order. The study examines the extent to which media technology contributes to maintaining the cultural identity and transnational relations of Diasporas in destination societies.The study concluded that communication technologies contributed to preserving the identity of expatriates and their relative cultural assimilation in local communities, However, it worked at the same time to exclude these minorities, which exacerbates ideological and cultural tensions, as well as the emergence of new concepts that increased the strength of the concept of diaspora